THE EFFECTS OF FOOD INTAKE AND ITS FAT COMPOSITION ON INTESTINAL ECHOGENICITY IN HEALTHY DOGS. Issue 5 (30th June 2016) - Gaschen, Lorrie; Granger, L. Abbigail; Oubre, Olivia; Shannon, Dylan; Kearney, Michael; Gaschen, Frederic
Abstract : Dogs presenting for ultrasonography due to suspected gastrointestinal disease might have residual ingesta and this could have an affect on the appearance of intestinal mucosa unrelated to pathology. The purpose of this prospective descriptive study was to determine effects of a recent meal consisting of the recommended daily fat content (meal 1) and a higher fat one (meal 2) on mucosal echogenicity in healthy dogs. Sixty client‐owned and clinically healthy dogs were recruited. Two meals, one with 15% fat dry matter basis (meal 1) and a second with 1.5 ml/kg body weight corn oil added to result in a range of 41–63% fat dry matter basis (meal 2), were fed 1 week apart after a 12 h fast. Mucosal echogenicity scores were assigned at fasting, immediate postprandial and at 60 min after each meal. Duodenal scores were significantly greater for meal 1 at 60 min ( P < 0.001) as opposed to fasting and immediate postprandial. With meal 2, the duodenal score was significantly different ( P < 0.001) at the immediate and 60‐min data point compared to meal 1. Jejunal scores were significantly greater for meal 1 at the 60‐min data point ( P < 0.001) as opposed to fasting and immediate postprandial. With meal 2, the jejunal score was significantly different ( P < 0.001) only at the 60‐min data point compared to meal 1. Intestinal mucosal echogenicity can be increased in healthy dogs after food intake, regardless of fat content. This effect should be taken into consideration when increased mucosal echogenicity is identified in clinical patients.